(untitled) (Journal of the College of Languages (JCL), 2021)
This paper examines the use of one of the most common linguistic devices which is hyperbole. It shows how hyperbolic devices are used as an aspect of exaggeration or overstatement for an extra effect in which the speaker can use hyperbole to add something extra to a situation in order to exaggerate his idea or speech. It is, like other figures of speech, used to express a negative or positive attitude of a specific unit of language. Thus, this paper is set against a background of using hyperbole concerning two main fields (advertisements and propaganda). So, the use of hyperbole will be implied by analyzing them concerning their meaning) literal and non-literal). Methodology of this study follows the specific model of analysis adopted from Barthes (1977) cited in Machin (2007).